Synthesis of 1,2,4-Trioxepanes and 1,2,4-Trioxanes via H2O2-Mediated Reaction of Tertiary Carbinols - Ravi, Makthala; Anand, Devireddy; Maurya, Ranjani; Chauhan, Parul; Naikade, Niraj K.; Shukla, Sanjeev K.; Yadav, Prem P. (Synlett, 2013)
A facile and efficient method for the synthesis of 1,2,4-trioxepanes and 1,2,4-trioxanes from different carbinols having cyclopropyl and phenyl substituents has been developed. The corresponding hydroxyhydroperoxides were synthesized from 30% H2O2 mediated reaction of carbinols in acidic conditions. This method provided access to novel 6,6-diaryl-substituted 1,2,4-trioxanes derived from benzilic acid.
Keywords: 1,2,4-trioxanes; 1,2,4-trioxepanes; hydrogen peroxide; carbinols; antimalarial